The Etymology of Old English *docga - Gąsiorowski, Piotr (de Gruyter, 2006)
This article explores the origin of English dog (OE *docga), generally regarded as a word of unknown origin. It is argued, on the basis of its morphology, that the word is a hypocoristic derivative of , an Old English colour adjective. The article suggests that the relation between OE and ‘frog’ is not an isolated irregularity but an example of a derivational process represented also by <dox : *docga> and possibly by other such pairs in Old English (e.g. <fox: *fogga>).

DOI: 10.1515/9783110186505.275
Keywords: Etymology; Old English; Germanic; Dog; Docga; Hund; Docgena; Middle English